2012
DOI: 10.3399/bjgp12x653642
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in primary care management of diabetes and cardiovascular disease in people with serious mental illness

Abstract: BackgroundPatients with serious mental illness (SMI) have high rates of cardiovascular disease (CVD). In contrast to widespread perception, their access to effective chronic disease management is as high as for the general population. However, previous studies have not included analysis by ethnicity. AimTo identify differences in CVD and diabetes management, by ethnicity, among people with SMI. Design and settingThree inner east London primary care trusts with an ethnically diverse and socially deprived popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Other studies produced findings consistent with ours [ 2 , 3 , 11 , 26 ] in terms of BP control in cardiovascular MM, but we were able to extend these findings by including respiratory and mental health comorbidities and epilepsy. In total, we analysed data for six non-cardiovascular MM and for each condition, we found a consistent association between additional co-morbidities and reductions in mean ‘‘SBP”.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies produced findings consistent with ours [ 2 , 3 , 11 , 26 ] in terms of BP control in cardiovascular MM, but we were able to extend these findings by including respiratory and mental health comorbidities and epilepsy. In total, we analysed data for six non-cardiovascular MM and for each condition, we found a consistent association between additional co-morbidities and reductions in mean ‘‘SBP”.…”
Section: Discussionsupporting
confidence: 85%
“…A systematic review of adherence to diabetes medication in people with SMI reported adherence rates between 51% and 85% . A study in East London found that people with diabetes and SMI were more likely to smoke and to be obese and less likely to have had retinopathy screening than those without SMI, and target blood glucose level was achieved by less than half of participants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research conducted in East London (Mathur et al . ) found that those with SMI and diabetes were more likely to smoke, be obese and less likely to have had retinopathy screening than those without SMI. In addition, less than half of the population met the glycaemic control target of HbA1c <7.5%, a standardized measure of glycaemic control and directly associated with the risk of diabetic complications (Diabetes UK, ).…”
Section: Diabetes Mellitus and Smimentioning
confidence: 99%